2021
DOI: 10.3389/fendo.2021.738138
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Scoring System for Predicting the Metastases of Posterior Right Recurrent Laryngeal Nerve Lymph Node Involvement in Patients With Papillary Thyroid Carcinoma by Preoperative Ultrasound

Abstract: ObjectiveOur goal was to investigate the correlation between papillary thyroid carcinoma (PTC) characteristics on ultrasonography and metastases of lymph nodes posterior to the right recurrent laryngeal nerve (LN-prRLN). There is still no good method for clinicians to judge whether a patient needs LN-prRLN resection before surgery, and we also wanted to establish a new scoring system to determine whether patients with papillary thyroid carcinoma require LN-prRLN resection before surgery.Patients and MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This study did not find a significant association between gender, age, tumor size, uni-multifocality, prelaryngeal lymph nodes metastasis, left CLN metastasis, and LN-prRLN metastasis. However, a significant association was reported by previous studies on PTC (14)(15)(16)(17). Using univariate and multivariate analyses, we confirmed that ETE, lateral lymph node metastasis, the number of metastatic LN-arRLN were independent predictors of LN-prRLN metastasis, which was consistent with previous reports (6,14,15,18).…”
Section: Discussionsupporting
confidence: 92%
“…This study did not find a significant association between gender, age, tumor size, uni-multifocality, prelaryngeal lymph nodes metastasis, left CLN metastasis, and LN-prRLN metastasis. However, a significant association was reported by previous studies on PTC (14)(15)(16)(17). Using univariate and multivariate analyses, we confirmed that ETE, lateral lymph node metastasis, the number of metastatic LN-arRLN were independent predictors of LN-prRLN metastasis, which was consistent with previous reports (6,14,15,18).…”
Section: Discussionsupporting
confidence: 92%
“…Gong Y and Ito Y’s research ( 19 , 20 ) shows that, compared with the nodules located at the middle pole of the thyroid gland, nodules at the upper pole and middle-upper third of the thyroid gland are extremely prone to LLNM. This is mainly because the lymphatic drainage system of the thyroid gland is similar to the venous drainage system ( 21 ). In our study, the prevalence of LLNM was 63.2% (i.e., in 50 out of 79 patients) in the upper pole or the upper part of the high plane of the isthmus of the thyroid gland, which was higher than the thyroid nodules in middle pole and isthmus (22.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the detection rate of LN involvement in the central compartment is lower than that in the lateral compartment during preoperative evaluation [ 18 ]. Lu et al suggested a scoring system for predicting the metastases of specific LN in the central compartment [ 19 ]. However, CND should be mandatory in PTC patients with lateral neck LN metastases to avoid persistent disease and false negative skip metastases.…”
Section: Discussionmentioning
confidence: 99%